Control of suddenly expanded flow - Khan, Sher Afghan; Rathakrishnan, E. (Emerald Group Publishing, 2006)
This paper presents an experimental investigation to study the effectiveness of micro jets under the influence of Over, Under, and Correct expansion to control the base pressure in suddenly expanded axi‐symmetric ducts.Four micro jets of 1 mm orifice diameter located at 90° intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed as active controls. The tests were conducted for Mach numbers 1.5, 1.3, 1.6, 1.8, 2.0, 2.5, and 3.0. The jets were expanded suddenly into an axi‐symmetric tube with cross‐sectional area 2.56 times that of nozzle exit area. The L/D ratio of the sudden expansion tube was varied from 10 to 1. From the present studies, it was found that the maximum increase in base pressure is 152 percent for Mach number 2.58. It is found that the micro jets do not adversely influence the wall pressure distribution. As a result of developments in space flights and missile technology, the base flows at high Reynolds numbers continues to be an important area of research. Our understanding of many features of base flows remains poor, due to inadequate knowledge of turbulence, particularly in the presence of strong pressure gradient. The paper shows that micro jets can serve as an effective controller raising the base suction to almost zero level for some combination for parameters. The nozzle pressure ratio has a definite role to play in fixing the base pressure with and without control. There is no adverse effect of the micro jets on the flow field in the duct.